P53 Entamoeba histolytica testing in the management of inflammatory bowel disease patients at university hospitals Leicester. (19th June 2022) - Pantzaris, Nikolaos; Tank, Vivek; O'Meara, Diane; Chiodini, Peter; Lim, Felicia; Martin, Vicky; Richards, Catherine; Thi, Aye Aye
Abstract : Introduction: Amoebic colitis can mimic inflammatory bowel disease (IBD) in clinical and endoscopical presentation. Back in 2018, the misdiagnosis of four patients with amoebic colitis as IBD at the University Hospitals of Leicester, prompted a change in practice. We began to screen IBD patients for Entamoeba histolytica prior to the immunosupression and offer empirical antimicrobial treatment. Methods: We conducted a retrospective electronic and case note review of IBD patients with positive amoeba immunofluorescence antibody test (IFAT) serology >1:80 from April 2019 through October 2020 during 2 audit cycles. Information including IBD type, travel history, stool E. histolytica DNA polymerase chain reaction (PCR), amoeba IFAT and Cellulose Acetate Precipitin test (CAP), endoscopic and histology data were collected. Results: A total of 59 IBD patients (23 in the original audit and 36 during the second cycle), were identified with positive IFAT, titers ranging from 1/80 to 1/320. 33 were female and mean age was 38.4, 38/59 patients had a diagnosis of Crohn's disease, 8/59 a diagnosis of ulcerative colitis and 3/59 a diagnosis of IBD Unclassified. All 59 patients had a negative CAP. 38/59 patients had a negative stool PCR and 21 were not tested. During the 2 nd audit cycle 8/36 patients underwent lower GI endoscopy at the time of the positive IFAT. From those, 1/8 had a macroscopically normal endoscopy and 7/8 had active colitis. All 36 histology samples (8/36 from endoscopy at the time of the IFAT and 28/36 from previous or subsequent endoscopies) were negative for amoeba trophozoites as reviewed by 2 different histopathologists. Conclusions: The recent change in practice and the new local guidelines are likely to have had an impact and we can confirm that there were no further cases of missed diagnosis of E. histolytica. It is a diagnostic challenge to differentiate IBD from amoebic colitis due to the similarity of symptoms and the endoscopic findings. Travel history is important and should be considered for any patient presenting with colitis. This project further consolidates that active screening for E. histolytica in patients presenting with colitis should be undertaken with serology and stool PCR in high risk areas.